The Effect of Company Size, Leverage, and Audit Quality on Earnings Management: Managerial Ownership as a Moderating Variable - Ayu Lisgianti; Edi Joko Setyadi; Eko Hariyanto; Hardiyanto Wibowo (Transpublika Publisher, 2026)
Earnings management remains a persistent issue in financial reporting, particularly in capital-intensive sectors such as the mining industry. Various firm characteristics and governance mechanisms are often examined to understand their role in influencing managerial incentives to manipulate earnings. This study investigates the effect of firm size, leverage, and audit quality on earnings management, with managerial ownership included as a moderating variable. This investigation utilizes secondary data extracted from the audited annual reports of mining enterprises listed on the Indonesia Stock Exchange (IDX) across the 2020–2024 observation window. The proposed hypotheses are evaluated through panel data estimation employing a Moderated Regression Analysis (MRA) specification. The empirical results demonstrate that leverage bears a statistically significant inverse relationship with earnings management, implying that greater debt exposure may curtail managerial latitude in financial reporting due to intensified scrutiny from creditors. In contrast, neither firm size nor audit quality exhibits a statistically discernible association with earnings management practices. Moreover, managerial ownership does not condition or moderate the relationships between firm size, leverage, audit quality, and earnings management. These findings underscore the salience of external disciplinary mechanisms, particularly creditor oversight, in constraining opportunistic reporting behavior, whereas managerial ownership appears to possess limited governance potency, largely attributable to its relatively marginal proportion within mining firms. Collectively, the study augments the extant literature by furnishing empirical insight into the effectiveness of governance mechanisms in mitigating earnings manipulation within Indonesia’s resource-based industrial sector.